THE FORMULATION AND EVALUATION OF 6-THIOGUANINE AS A NANOSTRUCTURE LIPID CARRIER FOR THE TARGETED DELIVERY OF BREAST CANCER - HASHIM, ALAA A.; ALTEMEMY, DHIYA; MOHAMMAD, HUSSEIN ABDELAMIR; MAHMOOD, HASANAIN SHAKIR; M. HUSSEIN, RADHWAN; REZAEI, MAHSA; KHOSRAVIAN, PEGAH (International Journal of Applied Pharmaceutics, 2024)
Objective: The main goal was to avoid all the problems associated with usual breast cancer treatment by using 6-thioguanine as a nanostructure lipid carrier (TG-NLCS). This was accomplished by administering an effective and targeted dose of 6-thioguanine (TG) to the tumour site using a long-lasting and biodegradable delivery system. Methods: A combination of heat homogenization and ultrasonication was used to implement the emulsification process. To obtain the optimal formulation, the prepared formulations were first assessed for particle size, Polydispersity Index (PDI), zeta potential, entrapment efficiency, and drug loading capacity. Additionally, a range of physicochemical characterization techniques were employed, including dissolution studies, melting point determination, Fourier-Transform Infrared (FTIR) spectroscopy, and Field Emission Scanning Electron Microscopy (FESEM), as well as cytotoxicity assessment of TG-NLCs in MCF-7 breast cancer cells. Results: The selected formula, TG03, showed a zeta potential of-13.5±0.27 mV and a particle size of 149±0.55 nm. This was further examined using a FESEM. In the in vitro drug release study, the formula demonstrated better-controlled drug release for 48 h in comparison to other formulations. In addition, the significant anti-proliferation activity of TG-NLCs against the MCF-7 breast cancer cell line. Conclusion: Nanostructured lipid carriers (NLCs) are one type of multifunctional nanoparticle that includes many combinations of lipids and medicines for various delivery routes.